TINJAUAN YURIDIS PENATAUSAHAAN KEUANGAN DAERAH DALAM MEWUJUDKAN GOOD GOVERNANCE BERDASARKAN PERATURAN WALIKOTA YOGYAKARTA NOMOR 136 TAHUN 2021 (STUDI DI KEMANTREN UMBULHARJO, KOTA YOGYAKARTA) - Margiyanto; Fransisca Romana Harjiyatni (Fakultas Hukum Universitas Janabadra, 2025)
This study aims to examine regional financial management in realizing good governance in the Yogyakarta City Government and to analyze the obstacles faced in regional financial management which focuses more on the stages of implementing regional financial administration in the Yogyakarta City Government. This type of research is a normative legal research, namely library legal research, with a statutory approach carried out by examining library materials and trying to synchronize the provisions contained in Government Regulation Number 12 of 2019 concerning Regional Financial Management with the Yogyakarta Mayor Regulation Number 136 of 2021 concerning the Regional Financial Management System and Procedures. To support and complete the information, interviews were conducted with selected sources in order to perfect information about various aspects related to the regional financial administration system and procedures. Data analysis uses a deductive thinking method. The results of the research show that the system and procedures for regional financial management at the general administration stage have been implemented based on the Regulation of the Mayor of Yogyakarta Number 136 of 2021 concerning the System and Procedures for Regional Financial Management. The obstacles encountered are human resource constraints, financial administration information systems, use of providers, and management of evidence of spending. These obstacles need to be considered so that they can realize better regional financial management in the future..